THE ROLE OF THE SAMARKAND AGRICULTURAL INSTITUTE IN TRAINING SPECIALISTS (1930–1990) - Botirjonovna, Begimova Ruxshona; qizi, Uralova Dilnura Samariddin; qizi, Buriyeva Sevinch Dilshod (Research Focus International Scientific Journal, 2026)
This article provides a scientific analysis of the historical role of the Samarkand Agricultural Institute in training qualified specialists for the agricultural sector of Uzbekistan during the period of 1930–1990. The study examines the conditions of the institute’s establishment, its academic programs, scientific and pedagogical activities, practice-oriented education system, and its connections with agricultural production. Furthermore, it highlights the institute’s contribution to the agrarian development of the republic through training specialists in agronomy, animal husbandry, veterinary science, irrigation, selection, and agricultural economics. The research findings demonstrate that the Samarkand Agricultural Institute was not only an educational institution but also one of the key centers for the scientific development of agriculture.